The potential of ecoenzymes on vegetative and generative growth in curly chili plants (Capsicum annuum) - Surtikanti, Hertien Koosbandiah; Kusdianti; Saidah , Salsabila Shafa (Applied Environmental Science, 2024)
Background: Red hot chili (Capsicum annum) is one of the important commodities for the community. The use of inorganic fertilizers in chili cultivation in the long run can disturb the soil balance. Therefore, it is necessary to make efforts to maintain and improve soil aggregation, so that soil particles more easily bind organic matter. One important effort is to apply organic fertilizer to the soil. One alternative liquid organic fertilizer that can be used is Ecoenzyme (EE). EE is the result of fermentation of organic kitchen waste such as leftover fruit and vegetable peels, molasses and water. This study was conducted to obtain the optimal concentration of EE on the growth and chlorophyll levels in Capsicum annum plants. Methods: There were 6 treatments in this study, namely E0 (no treatment as negative control), E1 (goat manure with soil: husk: fertilizer ratio of 1:2:1 as positive control), and different concentrations of EE, namely, E2 (EE 1 ml/1 liter of water), E3 (EE 5 ml/1 liter of water), E4 (EE 10 ml/1 liter of water) and E5 (EE 15 ml/1 liter of water). Findings: The results of significance data analysis with Duncan at the 5% level showed that treatment E1 was significantly different from the other treatments and treatment E4 showed different results but not significant with other EE treatments based on vegetative and generative growth parameters. Conclusion: The conclusion of this study is that the optimal concentration of EE to increase growth and chlorophyll levels in curly chili plants at a dose of EE 10 ml/1 liter of water. Novelty/Originality of this Study: The novelty of this investigation lies in its examination of the effects of ecoenzyme, an organic liquid fertilizer derived from fermented kitchen waste, on the growth and chlorophyll content of curly chili (Capsicum annuum) plants. This research is unique as it applies ecoenzyme to a horticultural crop that has not been extensively studied in this context, offering insights into sustainable agriculture practices and nutrient recycling.